Staphylococcal Panton-Valentine Leucocidin as a Major Virulence Factor Associated to Furuncles - Baba-Moussa, Lamine (Public Library of Science, 2011)
Panton-Valentine Leucocidin (PVL), one of the β-barrel pore-forming staphylococcal leucotoxins, is known to be associated to furuncles and some severe community pneumonia. However, it is still uncertain how many other virulence factors are also associated to furuncles and what the risk factors of furuncles are in immuno-compromised status of patients, especially the HIV (+) patients. In this paper, we use antigen immunoprecipitation and multiplex PCR approach to determine the presence of 19 toxins, 8 adhesion factors and the PFGE profiles associated to furuncles in three independent patient study groups of S. aureus (SA) isolates collected from the Cayenne General Hospital (French Guiana). The patient groups were made of: 16 isolates from HIV (−) patients, 9 from HIV (+) patients suffering from furuncles, and 30 control isolates from patients with diverse secondary infected dermatitis. Our data reveals that the majority (96%) of SA strains isolated from HIV patient-derived furuncles significantly produced PVL (p<10(−7)), whereas only 10% of SA strains produced this toxin in secondary infected dermatosis. A high prevalence of LukE-LukD-producing isolates (56 to 78%) was recorded in patient groups. Genes encoding clumping factor B, collagen- and laminin-binding proteins (clfB, cna, lbp, respectively) were markedly frequent (30 to 55%), without being associated to a specific group. Pulse field gel electrophoresis evidenced 24 overall pulsotypes, whereas the 25 PVL-producing isolates were distributed into 15 non clonal fingerprints. These pulsotypes were not specific PVL-producing isolates. PVL appears to be the major virulence factor associated to furuncles in Europe and in South America regardless of the immune status of the HIV patients.